2021
DOI: 10.1038/s41598-021-94038-2
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of Kabul Dhingri (Pleurotus eryngii) mushroom by standardizing protocols in subtropical zones of world

Abstract: The study is of great relevance with present day pandemic era where mushrooms have immunity enhancing properties and they convert agro-wastes into protein rich food. India is having a youth population of about 750 million and mushroom cultivation has good potential to contribute in national income as well as enhanced immunity. The key aspects undertaken during research were the spawn production, cultivation methodology, and the suitability of various factors affecting the production and yield attributes of Ple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…P . abieticola has a broad range of nutrient utilization capabilities and can grow well on both broadleaf and conifer substrates compared to other Pleurotus species ( Deora et al, 2021 ; Muswati et al, 2021 ; Oyetayo et al, 2021 ). Due to its ability to grow on waste products from conifer trees, as well as agricultural and forestry residues that are abundant in China, P .…”
Section: Discussionmentioning
confidence: 99%
“…P . abieticola has a broad range of nutrient utilization capabilities and can grow well on both broadleaf and conifer substrates compared to other Pleurotus species ( Deora et al, 2021 ; Muswati et al, 2021 ; Oyetayo et al, 2021 ). Due to its ability to grow on waste products from conifer trees, as well as agricultural and forestry residues that are abundant in China, P .…”
Section: Discussionmentioning
confidence: 99%
“…Patel and Trivedi (2014) also found that fresh fruit body yield and biological efficiency were obtained maximum by using 3 kg substrate quantity with 150 gm of spawn dose. Deora et al (2021) observed that 3 kg and 4 kg straw with 3 % spawn dose gave maximum yield and biological ef-…”
Section: Pleurotus Strain-pl-19-06mentioning
confidence: 96%
“…The mature mushroom was plucked by turning it clockwise from the base to uproot it. The harvested mushroom fruiting bodies were weighed for the calculation of the biological efficiency (Deora et al, 2021).…”
Section: Crop Management and Harvesting Of Mushroommentioning
confidence: 99%
“…King oyster mushrooms have a cylindrical, elongated stem and a small, tan coloured cap. They are cultivated using indoor techniques, often on supplemented sawdust or straw substrate (Deora et al, 2021).…”
Section: Mushroom Speciesmentioning
confidence: 99%